VALUE OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Desak Ayu Sriary Bhegawati; Ni Putu Yuria Mendra; Luh Pande Eka Setiawati; Putu Ayu Meidha Suwandewi (Bajang Institute, 2021)
The importance of disclosing corporate social responsibility reports in the company's annual report can indirectly affect the high value of the company. Profitability which in this study is proxied by ROE is the company's ability to generate profits based on certain share capital. This study aims to obtain empirical evidence regarding the effect of Corporate Social Responsibility on company value with profitability as a moderating variable.This research was conducted at manufacturing companies listed on the IDX in 2018-2020. The sampling method used was purposive sampling. The number of companies that meet the criteria is 78 companies that have data related to the variables used. Data collection was done by using documentation method. The data analysis technique used is the Moderated Regression Analysis (MRA) test. Based on the research results, it shows that Corporate Social Responsibility has a significant positive effect on company value. This study also found that the profitability proxied by ROE was able to moderate the influence of Corporate Social Responsibility on company value.